The legal protection of databases / Mark J. Davison. - Davison, Mark J. (Cambridge intellectual property and information law ;, 2003)
Mark Davison examines several legal models designed to protect databases, considering in particular the EU Directive, the history of its adoption and its transposition into national laws. He compares the Directive with a range of American legislative proposals, as well as the principles of misappropriation that underpin them. In addition, the book also contains a commentary on the appropriateness of the various models in the context of moves for an international agreement on the topic. This book will be of interest to academics and practitioners, including those involved with databases and other forms of new media.